Expression profiles of lncRNAs and their possible regulatory role in monocrotaline-induced HSOS in rats - Ismail, Mohammed; Zhang, Xi; Taha, Reham; Elhafiz, Muhanad; Zhang, Qianwen; Yousef, Bashir A.; Huang, Xin; Jiang, Zhenzhou; Zhang, Luyong; Sun, Lixin (Frontiers in Genetics, 2023)
Aims: Long noncoding RNAs (lncRNAs) have a contribution in the regulation of vital physiological processes and the pathogenesis of many diseases. Monocrotaline (MCT) can cause large-scale outbreaks of toxic liver disease in humans and animals as hepatic sinusoidal obstruction syndrome (HSOS). Although many experiments were performed to explain the pathogenesis, and treatment of MCT-induced HSOS, no studies were conducted on lncRNA roles on it. This research aimed to study the lncRNA-mRNA regulation network in MCT-induced HSOS in rats. Main methods: We established MCT-induced HSOS, and then carried out microarray for liver tissues of SD rats in an early HSOS model (MCT-12h treated and control groups) to investigate the differentially expressed lncRNAs and mRNAs in the early hepatotoxicity, followed by RT-PCR for selected lncRNAs, which were markedly changed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genome analysis were also conducted Key findings: 176 lncRNAs (63 down-regulated and 113 up-regulated) and 4221 mRNAs (2385 down-regulated and 1836 up-regulated) were differentially expressed in the MCT-treated group compared to the control group. According to biological processes in enriched GO terms, the positive regulation of Guanosine Triphosphate Phosphohydrolase, liver development, and the oxidative-reduction process had roles in hepatotoxicity. Pathway analysis revealed that metabolism pathways, Gap junction, and Ribosome biogenesis in eukaryotes had close relationships with MCT-induced hepatotoxicity. According to analysis, LOC102552718 might play an essential role in the hepatotoxicity mechanism by regulating Inositol 1,4,5-trisphosphate Receptor-1 (Itpr-1) expression. Significance: This study provides a basis for further research on the molecular mechanisms, and treatment of MCT-induced hepatotoxicity, especially in the early stage, which is pivotal to treat it successfully before irreversible liver damage occurs.